Avaliação do consumo alimentar e estado nutricional de crianças menores de dois anos de uma comunidade quilombola - Vasconcelos, Carliane Vanessa Souza (2022)
Epidemiological surveillance in Food and Nutrition is based on the Food and Nutrition Surveillance System, which aims to provide continuous information on the food and nutrition profile of the Brazilian population and the factors that influence it. The objective of this study was to evaluate the food consumption and nutritional status of children aged 0 to 23 months who live in the Quilombola Community of Córrego dos Iús. The methodological course is an exploratory, descriptive study, with a qualitative approach. The interviews were carried out with the mother, father or guardian of the child, acting as an informant in February 2021. We identified 11 children under two years of age in the community. Due to losses, refusals or the absence of the person responsible for the household, the studied sample consisted of 9 participants. Data collection took place through home visits, using anthropometric equipment (wooden infantometer and portable electronic scale), registration form and food consumption markers form of the Food and Nutrition Surveillance System. Nutritional status was classified according to the criteria of the World Health Organization, which recommends BMI-for-age cut-off points for children aged 0 to 2 years. Values that are between <Score-z-3 and >Score –z+3 to identify, respectively, cases of deficit or excess weight (BRASIL, 2011). Weight, height, age and sex data were processed in the DietSmart application to obtain anthropometric indices (https://www.dietsmartsystem.com/DietSmart/). From this information, we produced the following indicators: height for age, weight for age, weight for height, BMI for age (Z Score, WHO). In relation to food consumption, the data were evaluated according to the guidelines for the evaluation of food consumption markers in Primary Care. In which the indicators referring to children under six months of age on exclusive breastfeeding were used, in children aged between six and 23 months who are respectively in: continued breastfeeding, minimum food diversity, minimum frequency and adequate consistency, consumption of ultra-processed foods, organized according to the blocks of questions that make up the food consumption markers form (BRASIL, 2015). From the anthropometric assessment, we found that the most important nutritional problems were high weight for age (44.4%), risk of overweight for height and obesity for height presented respectively (11.1%), overweight for BMI by age (11.1%). Regarding food consumption, only 33% of the children were exclusively breastfed, and 50% of them were continuously breastfed. Inadequate iron intake was observed in about 84% of children. However, all children consumed beans (100%), but only one of the evaluated children consumed liver (16%). The consumption of ultra-processed foods presented 83%. The findings suggest that the population studied is undergoing a nutritional transition. It is necessary to consolidate public policies to improve the health of the studied community. We observed important risks of nutritional status and inadequacies in food consumption that; are compromising the health of the studied quilombola children.